The Chronology of Angiostrongylus vasorum (Baillet, 1866), Kamensky, 1905: Infection in Biomphalaria glabrata (Say, 1818) - T. A. Barçante; J. M. P. Barçante; L. Cardoso; R. N. Remedio; W. S. Lima (Journal of Parasitology Research)
The intermediate hosts of the French heartworm Angiostrongylus vasorum are aquatic and terrestrial gastropods. The present work is aimed at clarifying the sites of penetration and the migratory routes of A. vasorum in Biomphalaria glabrata snail tissues and evaluating their perilarval reaction with regard to the cellular composition and histological alterations involved in the gastropod response to infection. Biomphalaria glabrata snails were individually infected with 1000 first-stage larvae (L1) of A. vasorum each and killed at predetermined times after infection. Percutaneous infection occurred simultaneously with oral infection. Despite larval tropism to the fibromuscular tissue, some larvae were located in different tissues and organs. A perilarval reaction was observed around the larvae in a fibromuscular layer, appearing later around the larvae located in the viscera. The number of hemocytes surrounding the larvae increased gradually, forming a pregranuloma. Larval death and degeneration were not observed. No defined migratory pattern occurred, and larval development was apparently not associated with particular tissues or organs. In addition, the infection by A. vasorum induces a systemic mobilization of hemocytes in perilarval reaction.